Quality improvement in the aerospace industry: Investigation of the main characteristics - de Souza, João Paulo Estevam; Alves, João Murta; Silva, Messias Borges [UNESP] (Praise Worthy Prize, 2014)
This paper investigates the main characteristics, results, and factors that facilitate or complicate the implementation and maintenance of quality improvement programmes in the aerospace supply chain organisations in Brazil. This topic is extremely relevant to the scenario of actual aerospace supply chains, considering that organisations in this sector continuously invest in quality improvement programs, but face difficulties in evaluating the strategic effects on the product quality. We use a quantitative research methodology based on a survey for our investigation. We extensively review the literature to develop our measurement instrument and confirm its reliability and validity through an assessment by experts and a pilot test. The research results indicate that most organisations employ programmes based on the ISO 9001 and AS 9100 standards. We further describe the factors that facilitate or complicate the implementation or maintenance of the quality improvement programmes. We find that most organisations intend to either expand the actual programmes or implement new ones. Our findings suggest that, in general, the implementation of quality improvement programmes yield results beyond expectations in terms of product quality and the satisfaction of external customers.
Keywords: Aerospace; Improvement; Productivity; Quality; Survey